The EC and the Locational Choice of Swedish Multinational Companies - Birgitta Swedenborg (The Research Institute of Industrial Economics (IUI), 1988)
In a world with multinational companies (MNC's) changes such as those implied by the realization of EC's internal market will affect the locational choice made by geographically mobile MNC's. The reason is that the reduction of trade barriers within the EC puts non-EC members at a competitive disadvantage relative to EC members, thereby increasing the incentive to produce within the common market. This is true even though there may be no absolute increase in trade barriers for non-members. This (highly preliminary) paper suggests how the effects of the internal market on the location of production can be analyzed in a partial equilibrium framework of a firm serving many national markets and able to produce in different countries. It uses unique survey data on Swedish MNC production and trade for the period 1965-86 and draws on previous analysis of the earlier part of that data to indicate how important these effects may be empirically.
Keywords: F13; F23; 330; Multinational firms; European internal market; trade barriers; allocation of production; partial equilibrium; EU-Binnenmarkt; Multinationales Unternehmen; Schweden; EU-Staaten